Perencanaan Struktur Pondasi Gedung Madrasah Ibtidaiyah Miftahul Ulum Kecamatan Duduk Sampeyan Kabupaten Gresik dengan STAAD Pro - Ikhtisoliyah; Mohammad Rifki Arianto (Wahana Teknik, 2021)
The development of science and technology in the field of analysis and construction planning is currently increasing, especially foundations. The foundation is a building structure that is in direct contact with the ground. This is because the foundation serves to distribute the load of the building to the soil layer so that if it is deep planning and implementation is not done properly it will result in the failure of the structure above it. The development of a construction project such as the development of Madrasah Ibtidaiyah Miftahul Ulum which is located in the Duduk Sampeyan District of Gresik Regency requires many things to support from planning to implementation. The foundation used in the construction of the Madrasah Ibtidaiyah Miftahul Ulum building is a type of strauss foundation. The reason for using a strauss foundation is because of the cohesive soil condition so that there is a potential for foundation settlement to occur so that researchers feel the need to use this type of foundation. The structural planning will be analyzed using the STAAD Pro program. In this study, the results of the vertical loading analysis obtained a maximum vertical force value of Pu of 454.04 kN, Mux of 0.000049 kNm, and Muy of 0.99 kNm. In addition, the dimensions of a strong pile cap to withstand the load used reinforcement 16 x 200 mm with a pile cap type PC7 with dimensions of 0.45 m x 0.45 m and PC11 with a pile cap shear strength is 465,564 kN.